Spectral Studies of Co(II), Ni(II) and Cu(II) Complexes with o-(bis-Acetylacetonato) Phenylene Diamine - Thakur, S.N.; Brat Singh, Shiv; Kumar, Sanjay; Singh, S.P.; Anupama, Kumari (Asian Journal of Chemistry, 2010)
A series of the complexes of the type MLB2[M = Co(II), Ni(II) and Cu(II) ions, B = H2O, pyridine and α-picoline] have been synthesised with Schiff base as nitrogen and oxygen donor ligands. Characterisation of the ligand and the complexes has been done on the basis of elemental analysis, spectral studies, magnetic susceptibility and electrical conductivity measurements. The ligand has been found to coordinate through two nitrogen and two oxygen atoms. Since the complexes are found to be octahedral in nature the remaining two coordination sites of the metal are satisfied by oxygen of H2O and nitrogen of nitrogen donor molecules such as pyridine and α-picoline.